2015
DOI: 10.1007/s00040-015-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of subterranean gallery systems of soil-feeding termites Pericapritermes nitobei and Sinocapritermes mushae

Abstract: Soil-feeding termites are a critical trophic guild comprising more than a quarter of all termite species. Most soil-feeding termites build subterranean and diffuse gallery systems that are difficult to observe. In this study, we excavated the gallery systems of two soil-feeding termite species, Pericapritermes nitobei (Shiraki) and Sinocapritermes mushae (Oshima & Maki). Termite-harboring spaces were clusters of small cells connected with tunnels, with the cells usually adjacent to underground pieces of wood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…These mandibles have been hypothesised to be a defensive weapon, especially in tunnels 6,12 , where both termites and their enemies are confined to narrow spaces (e.g., approximately 2-mm wide, as reported for Pe. nitobei and Sinocapritermes mushae 19,38 ). Narrow tunnels limit termite movement as well as the gape of biting or slashing mandibles, thereby reducing their defensive performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mandibles have been hypothesised to be a defensive weapon, especially in tunnels 6,12 , where both termites and their enemies are confined to narrow spaces (e.g., approximately 2-mm wide, as reported for Pe. nitobei and Sinocapritermes mushae 19,38 ). Narrow tunnels limit termite movement as well as the gape of biting or slashing mandibles, thereby reducing their defensive performance.…”
Section: Resultsmentioning
confidence: 99%
“…nitobei is a soil-feeding termite that does not have a centralised nest; they distribute their eggs and larvae in subterranean tunnels beneath stones 19 . They generally forage on organic matter adjacent to plant roots and rarely appear on the ground surface 19 . Because Pe.…”
Section: Methods Termites and Antsmentioning
confidence: 99%
“…Termite functional groups are sorted based on their adaptation to the level of dietary substrate humification [ 46 ]. Group IIf termites use fresh litter biomass, a high-carbon, high-energy source that is available around trees, for their gardening activities [ 54 , 55 ], while most genera in group III use only litter biomass with a high degree of decomposition, which has low carbon and energy contents compared to fresh litter biomass [ 35 , 46 , 56 ]. These adaptations cause group III to have scattered colonies that are interconnected to one another and keep expanding over time to compensate for their low-energy diet, which contrasts with the localized spread of group IIf termites around trees, as indicated by the presence of galleries and runways on teakwood trunks.…”
Section: Discussionmentioning
confidence: 99%
“…Because the three monitored colonies had already reached the mature status, the number of their colonial individuals was not likely limited by colony developmental time. The global distribution of C. gestroi is highly associated with urbanization (Li et al 2013, Chouvenc et al 2015b, and few studies report on the presence of C. gestroi in forests; thus, C. gestroi may be more adaptive to the urban environment than to the forest environment. Haagsma and Rust (1995), who suggested the positive effect of urbanization on termite colony size, demonstrated that another subterranean termite, Reticulitermes hesperus Banks, has smaller colonies in less-disturbed areas but larger colonies in urban areas.…”
Section: Discussionmentioning
confidence: 99%